Optical coherence tomography in photodynamic therapy for subfoveal choroidal neovascularisation secondary to age related macular degeneration: a cross sectional study. Issue 3 (17th February 2005) - Sahni, J; Stanga, P; Wong, D; Harding, S
Abstract : Aims: To introduce new terminology and validate its reliability for the analysis of optical coherence tomography (OCT) scans, compare clinical detection of cystoid macular oedema (CMO) and subretinal fluid (SRF) with OCT findings, and to study the effect of photodynamic therapy (PDT) on the foveal morphology. Methods: Patients with subfoveal, predominantly classic choroidal neovascularisation (CNV) secondary to age related macular degeneration (AMD) undergoing PDT were evaluated with refraction protocol best corrected logMAR visual acuity (VA), slit lamp biomicroscopy, stereoscopic fluorescein angiography (FFA), and OCT. New terminologies introduced to interpret the OCT scans were: neuroretinal foveal thickness (NFT), bilaminar foveal thickness (BFT), outer high reflectivity band thickness (OHRBT), intraretinal fluid (IRF), subretinal fluid (oSRF), and vitreomacular hyaloid attachment (VMHA). Results: Fifty six eyes of 53 patients were studied. VA was better in eyes with a thinner outer high reflectivity band (OHRBT) (p = 0.02) and BFT (p = 0.05). BFT was less in eyes that had undergone a greater number of PDT treatments (p = 0.04). There was poor agreement between OCT and clinical examination in the detection of CMO and subretinal fluid (κ = 0.289 and κ = 0.165 respectively). To validate the interpretation and measurements on OCT, two groups of 20 scans were analysed by two independent observers. There was good agreement between the observers in the detection of IRF, oSRF, and VMHA (p<0.001). Measurements of NFT and BFT had a high reproducibility, and of OHRBT reproducibility was low. Conclusions: New terminology has been introduced and tested. OCT appears to be superior to clinical examination and FFA in the detection of CMO. In this study, better vision was associated with a thinner OHRBT and/or the absence of SRF giving insight into the biological effect of PDT.